Preliminary study on the physicochemical and microbiological qualities of overripe tempeh - Lim, Esther Shi Lin (2023)
Tempeh is a famous soy-based product originated from Indonesia with high nutritional content. The nutritional content of tempeh makes it a high-quality source of protein, which is an ideal choice for vegan as the meat-substitute product. There is also another variation of tempeh which is overripe tempeh. Fundamentally, it is just a tempeh with extended fermentation. With the presence of fresh tempeh and overripe tempeh, a comparison was done to understand which tempeh is better to be consumed in terms of its organoleptic properties and nutritional value. Results showed that overripe tempeh exhibited a darker yellowish colour followed by a slightly reddish hue and had a higher physicochemical properties and proximate composition as shown in Table 4.1, 4.2, and 4.3 respectively. For instance, titratable acidity (0.20%), moisture (58.05%), ash (1.61%), and carbohydrate (17.75%) content. In addition, overripe tempeh demonstrated a lower hardness (1.63 N), springiness (0.83), and cohesiveness (0.20) value, while having a higher fracturability (3.09N) as compared to fresh tempeh. Besides, most of the panellists from the sensory evaluation as shown in Figure 4.1 does not prefer the softer texture as well as the stronger taste of overripe tempeh due to its sourness, and bitterness when compared to fresh tempeh. Furthermore, fungal communities were the dominant iii communities for both tempeh during the fermentation process. However, bacterial communities would take over fungal communities in overripe tempeh during extended fermentation. Throughout the 14 days of cold storage (4℃), the microbial population of overripe tempeh started to decline significantly on day 7 during shelf-life analysis as shown in Table 4.5. Future study would emphasise on a detail analysis of the changes in nutritional content and composition of microbial community.